Corporate Governance, Institutional Ownership, and Their Effects on Financial Performance - Hykaj, Kristal (European Scientific Journal, ESJ, 2016)
This paper studies the 105 U.S. Equity Real Estate Investment Trusts for the period of 2007-2012, and explores the relationship between corporate governance, institutional ownership, and financial performance. The results are conclusive and show that the presence of women on the board of directors as well as the choice to opt for a classified board enhances the returns on assets and returns on equity. The second finding of this paper is that the percentage of stocks owned by the top 10 institutions, between the levels of 30% and 50%, are associated with higher returns on assets and returns on equity.